An Empirical Framework Design to Examine the Improvement in Software Requirements through Negotiation - Ahmad, S.; Muda, N. A. (The Society of Digital Information and Wireless Communications, 2011)
Negotiation is one promising effort during requirements elicitation process to improve the quality of software requirements. When negotiation is claimed beneficial theoretically, it is important that the deployment of negotiation is examined and the effectiveness of negotiation is evaluated through empirical study. This paper aims at providing an empirical framework design to examine the improvement in software requirements through negotiation. Besides, it elaborates the relevance of negotiation in requirements elicitation process and its effectiveness. An empirical study method is imposed to design the framework. The design is carefully established based the selection of population and participants, the experimental protocol, threats to validity and justification of measures.